1994
DOI: 10.1093/ije/23.4.782
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stunting and Recovery from Stunting in Northwest Uganda

Abstract: These results suggest that, in this population, linear growth is influenced by environmental factors. It is a dynamic process continuing beyond the first 2-3 years of life, and the probability of catching up is very similar across all age groups < 5 years old. Recovery from stunting is more associated with mother's education than with income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 0 publications
4
29
0
1
Order By: Relevance
“…The trend was similar to findings on children in the general population from previous studies [9,31,32,33]. One of the studies showed that the prevalence of moderate and severe forms of malnutrition was high in children aged 13 to 36 months [31].…”
Section: Age and Gender Of The Childsupporting
confidence: 88%
See 1 more Smart Citation
“…The trend was similar to findings on children in the general population from previous studies [9,31,32,33]. One of the studies showed that the prevalence of moderate and severe forms of malnutrition was high in children aged 13 to 36 months [31].…”
Section: Age and Gender Of The Childsupporting
confidence: 88%
“…Prevalence of malnutrition significantly reduced with increase in SES. Earlier studies in Uganda and other countries showed that households with higher SES, have a lower prevalence of stunted children [9,32,33,36]. The burden of orphans (defined in this study as children who had lost both parents) and being widowed especially for female headed households jeopardizes the health and nutritional well-being of children [37].…”
Section: Socio-economic Factorsmentioning
confidence: 91%
“…Our previous work in a rural setting in Central Uganda (5) with younger children (<30 months) found a significant and positive association between the level of education of the mother and the health and nutritional status of the children. Other researchers from Uganda (13,18) and Ghana (19) have also noted an important association between the mothers' education on the child's nutrition status.…”
Section: Discussionmentioning
confidence: 93%
“…This Table 2 Estimated regression coefficients of binary logistic regression model (BlogM) for child malnutrition status defined as heightfor-age Z-score less than −2.00, the corresponding odds ratios (ORs), and adjusted predicted proportion (APP) of malnourished children from nominal-scale multiple classification analysis (NS-MCA) model, BDHS 2011 (Continued) Note: η i and β i indicates priority indices before and after the adjustment of other predictors respectively study also found that mothers with adequate nutrition status are less likely to have stunted children. Household factors are strong predictors of children nutritional status [42,43]. Usually, children in households having higher income have better nutritional status than that of lower income households.…”
Section: Discussionmentioning
confidence: 99%